Deferred Tax Accounting Concepts and Their Bond to the Accounting Ideologies - A. A. Aksent’ev (Учёт. Анализ. Аудит, 2021)
Deferred taxes are an important object of accounting observation to judge the degree of discrepancies between financial and tax accounting. Meanwhile, the information discloses to users the effects arising from the tax planning tools usage for corporate management and forecasting cash outflows associated with the payment of income tax in the future. The paper formalized two concepts of accounting for deferred taxes in the form of models: temporary and timing differences associated with accounting ideologies. The author ha structured the logic of reflecting deferred taxes on accounting accounts using the balance sheet and “cost” methods. Analysis of foreign experience and domestic practice made it possible to conclude that there are controversial issues on the assessment of deferred taxes in reporting, including at present value. Also, the author revealed discrepancies in Russian Accounting Standard (PBU) 18/02 which were conceptually different from a similar international standard and conflicting with it in a number of theoretical and methodological positions. The research results are aimed at scientific and practical workers in the field of financial accounting, taxation and audit.